A structured classification of the types of pain research studies accessed by different health professionals involved in pain management. Issue 4 (November 2020) - Arumugam, Vanitha; MacDermid, Joy C; Grewal, Ruby; Uddin, Zakir
Objectives: The aim of this study was to describe the information access behaviours of clinicians involved in pain management with respect to their use of a pain evidence resource and to determine the areas of professional differences. Methods: Users (n = 258) of a free pain evidence alerting service (PAIN + ) were enrolled in this study. The users regularly received email alerts about newly published clinical articles about pain that were pre-appraised for scientific merit and clinical relevance. A sample of up to 10 abstracts retrieved by each user were retrieved and classified using a descriptive classification system to describe the types of research, pain subtypes, interventions and outcomes that were reported in the accessed studies. Frequencies and chi-square tests were performed to compare access behaviours across professions. Results: A total of 258 participants viewed 2311 abstracts. More than 52% of abstracts viewed were primary clinical studies; the majority (87%) addressed treatment effectiveness and were quantitative research (99.8%). The most commonly accessed clinical topic (58%) related to musculoskeletal pain and the most accessed pain type was chronic pain (76%). Drugs, injections and rehabilitation therapy were most commonly addressed in accessed intervention studies. Differences in professional focus were reflected in access: physicians/nurses accessed studies on injections (23%) and drugs (26%) and nurses accessed surgical studies, whereas other professions rarely did. Physiotherapists (PTs) and occupational therapists (OTs) preferentially accessed studies on rehabilitation. OTs and psychologists preferentially accessed the available studies on cognitive interventions; OTs accessed more ergonomic studies. Psychologists most accessed educational and psychosocial intervention studies. There were no differences in access across professions to multidisciplinary interventions. Conclusion: While access partially reflects the content of the pain repository, professional differences in access were evident that related to the nature of the intervention, type of pain and the research design. Multidisciplinary evidence repositories may need to consider how to include and meet varied information needs.